Tourism Area Life Cycle (Talc) as A Planning Strategy for Ir. H. Djuanda Grand Forest Park in Bandung City - Dzaky Huda Ari Sumenang Putra; Bangun Permadi; Annisa Febrianti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Ir. H. Djuanda Grand Forest Park serves a dual role as both strategic ecotourism and conservation area. The successful revitalization in 2023 was marked by a surge in visitors, reaching nearly 600,000 people in 2024, significantly exceeding the target of 450,000. While this substantial increase indicates successful revitalization, it creates an urgency to analyze sustainability and the potential risk of overtourism within the conservation zone. This study aims to analyze Tahura's position on the Tourism Area Life Cycle (TALC) Model and formulate its planning strategies. The research employs a descriptive qualitative approach utilizing TALC and SWOT (IFAS/EFAS) analysis for strategy formulation. The findings indicate that Tahura is in the rejuvenation stage of the TALC cycle and is positioned in Quadrant III (Weakness to Opportunity) of the SWOT analysis. Based on these findings, four main strategies are recommended to achieve sustainable rejuvenation: determining the area's carrying capacity, improving supporting facilities (footpaths and sanitation), strengthening local community empowerment, and formulating long-term policies that balance the functions of conservation, tourism, and social welfare.